POTENTIAL OF Spirulina sp. FOR REMEDIATING POLLUTANTS IN AQUACULTURE WASTEWATER AND PRODUCING PHYCOCYANIN - Dewi, Resti Nurmala (Indonesian Fisheries Research Journal, 2024)
The sustainability of aquaculture wastewater treatment is challenging because it has a negative impact on the ecosystem if directly discharges to the environment. Aquaculture wastewater consists of high pollutants loading such as ammonia, phosphor, nitrate, and chemical oxygen demand. To offset the downsides of aquaculture effluent, effective solutions are required. Spirulina sp. is as microalgae that convert nutrients in the wastewater and dissolve carbon into microbial biomass with value such as phycocyanin which can be employed as food, cosmetics, feed, and pharmacy feedstock. The effects of light intensity (6,000 - 10,000 lux) and urea addition (20-100 ppm) on biomass production, COD reduction, and phycocyanin yield were investigated in this study. For 10 days, Spirulina sp. was grown in a batch reactor at 25-27°C with a ratio of 30% inoculum and 70% wastewater under continuous aeration. Spirulina sp. produced the most biomass at 8,000 lux with the addition of 60 ppm of urea accounting for 0.71±0.14 g/L (P > 0.05). Meanwhile, the maximum phycocyanin concentration was 4.21±0.132% at 7,000 lux and 80 ppm urea (P > 0.05) with 96.51% of chemical oxygen demand reduction (P < 0.05). The outcomes of this study highlight the potential of aquaculture effluent to produce valuable microalgal biomass and phycocyanin, which can be used to generate lucrative products.